Twin pregnancy reduction is not an ‘all or nothing’ problem: a response to Räsänen - Begović, Dunja (Journal of medical ethics, 2022)
In his paper, ‘Twin pregnancy, fetal reduction and the ‘all or nothing problem’, Räsänen sets out to apply Horton’s ‘all or nothing’ problem to the ethics of multifetal pregnancy reduction from a twin to a singleton pregnancy (2-to-1 MFPR). Horton’s problem involves the following scenario: imagine that two children are about to be crushed by a collapsing building. An observer would have three options: do nothing, save one child by allowing their arms to be crushed, or save both by allowing their arms to be crushed. Horton offers two intuitively plausible claims: (1) it is morally permissible not to save either child and (2) it is morally impermissible to save only one of the children, which taken together lead to the problematic conclusion that (3) if an observer does not save both children, then it is better to save neither than save only one. Räsänen applies this problem to the case of 2-to-1 MFPR, arguing ultimately that, in cases where there is no medical reason to reduce, the woman ought to bring both fetuses to term. We will argue that Räsänen does not provide adequate support for the claim, crucial to his argument, that aborting only one of the fetuses in a twin pregnancy is wrong, so the ‘all or nothing’ problem does not arise in this context. Furthermore, we argue that the scenario Räsänen presents is highly unrealistic because of the clinical realities of 2-to-1 MFPR, making his argument of limited use for real-life decision making in this area.